First check the difference between terms:
[tex]\{1-(-3),5-1,9-5,\ldots\}=\{4,4,4,\ldots\}[/tex]
So every term differs by 4. The first term in the sequence is [tex]a_1=-3[/tex]. Recursively, the sequence is given by
[tex]\begin{cases}a_1=-3\\a_n=a_{n-1}+4&\text{for }n>1\end{cases}[/tex]
Then
[tex]a_2=a_1+4[/tex]
[tex]a_3=a_2+4=a_1+4(2)[/tex]
[tex]a_4=a_3+4=a_1+4(3)[/tex]
and so on, with the general rule
[tex]a_n=a_1+4(n-1)\implies a_n=4n-7[/tex]
Then the 250th term of the sequence would be
[tex]a_{250}=4(250)-7=993[/tex]